Correlation between the length from the elbow to the distal interphalangeal joint of the little finger and the length of the intramedullary nail selected for femoral fracture fixation. Issue 11 (November 2018) - Alao, Uthman; Liew, Ignatius; Yates, Jonathan; Kerin, Cronan
Abstract: Aim: To determine whether there is a correlation between the length of forearm to the distal interphalangeal joint (DIPJ) of the little finger and length of antegrade intramedullary (IM) femoral nails in adults. Study Design and Methods: Measurements from the tip of the olecranon to the DIPJ of the ipsilateral upper limb was taken in 30 patients undergoing antegrade IM femoral nails. The length of the IM nails inserted was determined by intra-operative measurements using a guide wire. The two measurements were analysed for correlation and mean difference. Results: The mean forearm to DIP of little finger length was 38.86 with a standard deviation of 2.83. The mean IM length and standard deviation were 38.56 and 2.77 respectively. The difference between the two means 0.3 (95% CI). Correlation testing between the two variables shows a positive relationship (Pearson Correlation factor of 1). The scatter plot shows a positive linear relationship. Conclusions: Length of the forearm from the tip of the olecranon to the DIP joint of the little finger represents the ideal length of IM nail for the femur. It can be readily performed with the use of a tape measure and can serve as a useful adjunct to determining ideal length in cases where the contralateral femur cannot be used.